[LABOR RELATIONS SEMINAR PROPOSAL] - MILITA P (Tufts Archival Research Center, 2007)
Proposal from Ogilvy and Mather for a labor relations seminar at the Tobacco Institute (TI). Cites the need for TI staff to understand and be 'sensitized' to the basics of labor relations to proceed in plans for coalitions on workplace. Details planned seminar, including speakers from various AFL-CIO organizations and schedule. Presents proposed costs.